2017
DOI: 10.1051/mfreview/2017009
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and field assisted sintering of cerium-doped YSZ ceramic nanoparticles obtained via a hydrothermal process

Abstract: Abstract. Owing to its extraordinary range of properties, yttria-doped zirconia holds a unique place among the ceramic oxide systems. To improve the properties for some specific custom design applications, co-doping with other rare earth oxides such as ceria is needed. The aim of this paper is to identify the correlations between the phase composition evolution with increasing thermal treatment temperature in order to establish the thermal stability in connection with the ceria content and how does it influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Melting point, • C 2700 Evaporation rate µm/h × 10 −5 at 1650 • C 670 Density, g/cm 3 5.6 at 1927 However, at temperatures above 1200 • C in the long term, YSZ loses its phase stability but the main critical issue is calcium-magnesium-alumino-silicate (CMAS) attack that lowers the thermal insulating power [18,19]. Therefore, it is desired to develop new TBCs that can operate at a temperature above 1200 • C. An actual research topic is doping ZrO 2 ceramics with different rare earth oxides due to their high temperature transformation and the low thermal conductivity, which allow to increase the operating temperatures of turbines.…”
Section: Zro 2 Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Melting point, • C 2700 Evaporation rate µm/h × 10 −5 at 1650 • C 670 Density, g/cm 3 5.6 at 1927 However, at temperatures above 1200 • C in the long term, YSZ loses its phase stability but the main critical issue is calcium-magnesium-alumino-silicate (CMAS) attack that lowers the thermal insulating power [18,19]. Therefore, it is desired to develop new TBCs that can operate at a temperature above 1200 • C. An actual research topic is doping ZrO 2 ceramics with different rare earth oxides due to their high temperature transformation and the low thermal conductivity, which allow to increase the operating temperatures of turbines.…”
Section: Zro 2 Propertiesmentioning
confidence: 99%
“…Necessity for better performance and efficiency in applications across stationary power plants, aerospace and automotive industries has led to the development of thermal barrier coatings (TBCs) and multi-layer coating systems over the last 50 years [1]. During recent years it was demonstrated that co-doping of zirconia ceramics with rare earth oxides (REOs) may avoid grain size coarsening due to interface segregation, enhancing its ionic conductivity and sinterability [2,3]. The co-doping of zirconia with different REOs was reported to improve the thermal properties of thermal barrier coatings and oxidation properties due to reduction of mechanical stresses and porosity in the oxide layers [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Fang et al [58] showed enhanced densification of zirconia containing ceramic matrix composites by microwave processing. Tamburini [64]. The hydrothermally synthesized powders after were mixed with a solution containing 6 wt% polyvinyl alcohol as binder and spray dried using a LabPlant spray drier system (air speed of 3.5 m/s at evacuation and feeding rate of 617 ml/h using a 0.5 mm nozzle).…”
Section: New Sintering Methods Of Rare Earth Doped Zirconiamentioning
confidence: 99%
“…Table 2 depicts the various parameters/features associated with some of the synthesis methods for spinel formation and also includes the challenges associated with each methods. 138,139 Solid-state reactions are not ideal for producing reactive and fine MgAl 2 O 4 spinel powders because calcination at high temperatures causes grain growth and severe agglomeration of MgAl 2 O 4 particles. Spinel powder (MgAl 2 O 4 ) can be made by milling MgO and Al 2 O 3 in a highenergy ball mill, followed by calcination to reduce the temperature of the solid-state reaction.…”
Section: Comparison Among Different Synthesis Routesmentioning
confidence: 99%